Providing Guidance on Promoting Balanced and Nutritious Diet of Student of TKIT Al-Islah Gorontalo - Bait, Yoyanda; Dahlan, Sakinah Ahyani (Jurnal Pengabdian Masyarakat Teknologi Pertanian, 2023)
The objective of this initiative is to impart knowledge about nutritious food to children between the ages of 4 and 6 who attend TKIT Al-Islah Gorontalo. The study employs a descriptive research approach, employing qualitative data collection methods such as interviews and documentation. The outreach efforts revealed that the young participants, totaling 100 kindergarten children aged 4 to 6, displayed eagerness in engaging with the educational content, as evidenced by positive feedback. The educational content covers topics such as introducing what should be included on a plate during meals, promoting healthy snacks, incorporating songs about nutritious food, and concluding with interactive games centered around healthy eating. Keynote: healthy food; healthy snacks